Improved Aqueous Solubility and Antihypercholesterolemic Activity of Ezetimibe on Formulating with Hydroxypropyl-β-Cyclodextrin and Hydrophilic Auxiliary Substances - Srivalli K.M.R.; Mishra B. (My University, 2025)
The purpose of this study was to improve the aqueous solubility, dissolution, and pharmacodynamic properties of a BCS class II drug, ezetimibe (Eze) by preparing ternary cyclodextrin complex systems. We investigated the potential synergistic effect of two novel hydrophilic auxiliary substances, d-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) and l-ascorbic acid-2-glucoside (AA2G) on hydroxypropyl-β-cyclodextrin (HPBCD) solubilization of poorly water-soluble hypocholesterolemic drug, Eze. In solution state, the binary and ternary systems were analyzed by phase solubility studies and Job’s plot. The solid complexes prepared by freeze-drying were characterized by Fourier transform infrared (FTIR), differential scanning calorimetry (DSC), powder X-ray diffraction (XRD), nuclear magnetic resonance (NMR), and scanning electron microscopy (SEM). The log P values, aqueous solubility, dissolution, and antihypercholesterolemic activity of all systems were studied. The analytical techniques confirmed the formation of inclusion complexes in the binary and ternary systems. HPBCD complexation significantly (p < 0.05) reduced the log P and improved the solubility, dissolution, and hypocholesterolemic properties of Eze, and the addition of ternary component produced further significant improvement (p < 0.05) even compared to binary system. The remarkable reduction in log P and enhancement in solubility, dissolution, and antihypercholesterolemic activity due to the addition of TPGS or AA2G may be attributed to enhanced wetting, dispersibility, and complete amorphization. The use of TPGS or AA2G as ternary hydrophilic auxiliary substances improved the HPBCD solubilization and antihypercholesterolemic activity of Eze. © 2015, American Association of Pharmaceutical Scientists.